İdari yargıda “ısrar” (direnme) kararının şekil ve içerik bakımından niteliği - (:unkn) unknown (My University, 2012)
2577 sayılı İdari Yargılama Usulü Kanunu’na göre ilk derece mahkemelerince verilen kararlar Danıştay’da temyiz edilir. Temyiz incelemesi sonucunda Danıştay ilk derece mahkemesinin kararını bozar ya da onar. Bozma üzerine dosya ilk derece mahkemesine gönderilir. İlk derece mahkemesi bozma kararına uyabileceği gibi, ilk kararında ısrar da edebilir. Bu çalışma kapsamında, Danıştay ve Yargıtay kararları ışığında, ısrar kararlarının şekil ve içerik bakımından niteliği incelenmektedir.

In accordance with the Code of Administrative Procedure No. 2577, the appeals brought against the judgments rendered by the court of first instance are reviewed by the Council of State. As a result of the appellate review, the Council of State may either reverse or approve the lower court's judgment. In the event of reversal, the file is remanded to the court of first instance. The court of first instance may comply with the reversal decision, or otherwise may insist on its prior decision. In the scope of this paper, the characteristics of insistence decisions in terms of form and substance are examined in the light of Council of State and Court of Appeals decisions.
Keywords: Hukuk